Hongos micorrícico-arbusculares asociados a Chenopodiaceae en dos ambientes salinos de Córdoba - Becerra, Alejandra (2016)
Arbuscular mycorrhizal fungi associated with Chenopodiaceae from two saline environments of Cordoba province. Arbuscular mycorrhizal fungi (AMF) colonize approximately 82% of land plants in every ecosystem, even in extreme conditions such as saline soils. In the present work we report the arbuscular mycorrhizal colonization and its vertical root concentration in four Chenopodiaceae plants species (Allenrolfea patagonica, Atriplex argentina, Heterostachys ritteriana and Suaeda divaricata) at five different soil depths in two salines of central Argentina. All the plant species showed mycorrhizal colonization and varied significantly among plant species and sites for all soil depths. Atriplex argentina presented the highest mycorrhizal colonization at almost all soil depths (0-50 cm). In all plant species root concentration decrease as depth increases at both sites. The presence of mycorrhizal roots in the deeper layers of soil in the four Chenopodiaceae plants species, shows that these fungi are tolerant to live in the saline soils of central Argentina.